KONTRIBUSI PENGUASAAN KOSAKATA BIDANG LINGKUNGAN HIDUP TERHADAP KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VIII SMP NEGERI 6 PARIAMAN - Syafitri, Rosa Andria; Nursaid, Nursaid (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT The purpose of this research there are three. First, describe the environmental field vocabulary mastery of grade VIII SMP Negeri 6 Pariaman. Second, it describes the text of the news writing skills of students of class VIII SMP Negeri 6 Pariaman. Third, vocabulary mastery skills contribution to analyze the field of the environment against the text of the news writing skills of students of class VIII SMP Negeri 6 Pariaman. This type of research quantitative descriptive method. The design used in this research is the design korelasional. This research population is grade VIII SMP Negeri 6 Pariaman, i.e. 70 students. The sample in this research are determined using total sampling total sample that is equal to the number of population that is 70 students. Research data is vocabulary mastery test scores field environment and score news writing skills text.  Research instrument is the objective tests to measure mastery of the vocabulary of the field of environmental and performance tests for measuring writing skills text news. The results of the research there were three. First, mastery of the vocabulary of the field of the environment class VIII students of SMP Negeri 6 Pariaman are on good qualification. Secondly, the text of the news writing skills of students of class VIII SMP Negeri 6 Pariaman are on good qualification. Third, vocabulary mastery of the field of the environment account for 58.98% against the text of the news writing skills of students of class VIII SMP Negeri 6 Pariaman.               Kata Kunci: Kontribusi, Penguasaan Kosakata Bidang Lingkungan Hidup, Keterampilan Menulis Teks Berita